Grounds of changemanagement - Gál, Zsuzsa (International Journal of Engineering and Management Sciences, 2020)
Organisations of the 21st century exist in a permanent change. Change management in business management deals with the analysis of directed and planned changes. However, it does not consider spontaneous changes.Change has been addressed in social science since the 1970s and is of growing importance. As in many cases adapting to the change is crucial for the organisations to survive. With the changeThese spontaneous changes are chaotic processes that are carried out without control. In this paper I present the evolution of changemanagement, and the most important questions of changes.